Effects of octahedral molecular sieve on treatment performance, microbial metabolism, and microbial community in expanded granular sludge bed reactor. (15th December 2015) - Pan, Fei; Xu, Aihua; Xia, Dongsheng; Yu, Yang; Chen, Guo; Meyer, Melissa; Zhao, Dongye; Huang, Ching-Hua; Wu, Qihang; Fu, Jie
Abstract: This study evaluated the effects of synthesized octahedral molecular sieve (OMS-2) nanoparticles on the anaerobic microbial community in a model digester, expanded granular sludge bed (EGSB) reactor. The addition of OMS-2 (0.025 g/L) in the EGSB reactors resulted in an enhanced operational performance, i.e., COD removal and biogas production increased by 4% and 11% respectively, and effluent volatile fatty acid (VFA) decreased by 11% relative to the control group. The Biolog EcoPlate™ test was employed to investigate microbial metabolism in the EGSB reactors. Results showed that OMS-2 not only increased the microbial metabolic level but also significantly changed the community level physiological profiling of the microorganisms. The Illumina MiSeq high-throughput sequencing of 16S rRNA gene indicated OMS-2 enhanced the microbial diversity and altered the community structure. The largest bacterial genus Lactococcus, a lactic acid bacterium, reduced from 29.3% to 20.4% by abundance in the presence of 0.25 g/L OMS-2, which may be conducive to decreasing the VFA production and increasing the microbial diversity. OMS-2 also increased the quantities of acetogenic bacteria and Archaea, and promoted the acetogenesis and methanogenesis. The X-ray photoelectron spectroscopy illustrated that Mn(IV)/Mn(III) with high redox potential in OMS-2 were reduced to Mn(II) in the EGSB reactors; this in turn affected the microbial community. Graphical abstract: Highlights: OMS-2 nanoparticles improved the performance of EGSB reactor. OMS-2 enhanced the microbial diversity and altered the community structure. The dominant bacterial genus Lactococcus was significant inhibited by OMS-2. OMS-2 may affect the microbial community via dissimilatory Mn(IV) reduction.